Teaching botany in non-formal spaces: perceptions of elementary school students in a field class (Research, Society and Development, 2022)
The current scenario of demotivation and disinterest on the part of students constitutes a major obstacle to the Teaching of Sciences. Following this trend, the study of plants has been facing the same problems. The memoristic teaching and full of a complex vocabulary no longer has meaning for the students. In this scenario, non-formal teaching spaces emerge as a possibility to provide a more attractive and meaningful learning. In this work, we sought to analyze the impressions and memories of students about a field class in a Botanical Garden. To this end, it was proposed to a class of 15 students, of the 6th year of Elementary School, of a public school of Santa Maria/RS the visit to the Botanical Garden of UFSM. To analyze the students' perceptions about the activity, questionnaires were applied with three open questions, one month after the visitation. Most students signaled contentment with the activity in non-formal space and demonstrated to appreciate the landscape and plant species presented. The field exit presented potential for the development of learning beyond conceptual, impacting on the attitudes of the students. There was emphasis on exotic plants that were the most remembered by students. However, even though there was memory about the species presented, the number of plants mentioned was still low. These results indicate the importance of offering activities in a natural environment, thus enabling students to have greater contact with plant biodiversity.